2019
DOI: 10.1186/s40008-019-0154-2
|View full text |Cite
|
Sign up to set email alerts
|

Does energy-environmental Kuznets curve hold for Ethiopia? The relationship between energy intensity and economic growth

Abstract: Energy plays critical role in bringing the sustainable development. However, when not used efficiently, its negative consequences on any economy is enormous. This could be related to threatening the sustainable development of the economy, energy security and worsening the environmental conditions (Adom and Kwakwa 2014). Challenges like climate change and energy security that world economy is facing the in the twenty first century is mainly due to energy consumption. Since anthropogenic emissions of carbon diox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 75 publications
1
20
0
Order By: Relevance
“…The results of this research are similar to the findings reported by Kurniawan and Managi ( 2018 ). Furthermore, it is also consistent with various studies that investigated the relationship between urbanization and carbon emissions, among others, Ahmad et al ( 2019 ) in China, Zhang et al ( 2019 ) in the Asian region, Anwar et al ( 2019 ) in 59 countries (low-middle-upper income) including Indonesia, Hundie and Daksa ( 2019 ) in Ethiopia, Kasman and Duman ( 2015 ) in EU countries, and Ozatac et al ( 2017 ) in Turkey, shows that increasing urbanization will encourage increasingly massive use of energy which has an impact on environmental damage. The urbanization in Indonesia has grown significantly along with the rapid growth of the industry.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The results of this research are similar to the findings reported by Kurniawan and Managi ( 2018 ). Furthermore, it is also consistent with various studies that investigated the relationship between urbanization and carbon emissions, among others, Ahmad et al ( 2019 ) in China, Zhang et al ( 2019 ) in the Asian region, Anwar et al ( 2019 ) in 59 countries (low-middle-upper income) including Indonesia, Hundie and Daksa ( 2019 ) in Ethiopia, Kasman and Duman ( 2015 ) in EU countries, and Ozatac et al ( 2017 ) in Turkey, shows that increasing urbanization will encourage increasingly massive use of energy which has an impact on environmental damage. The urbanization in Indonesia has grown significantly along with the rapid growth of the industry.…”
Section: Resultssupporting
confidence: 86%
“…Research on EKC then developed further by using various variables as proxies, including energy (Destek and Sarkodie 2019 ; Hundie and Daksa 2019 ; Usman et al 2019 ), financial sector development (Tamazian and Rao 2010 ; Charfeddine and Ben 2016 ; Aye and Edoja 2017 ), government performance (regulation, corruption index, education index) (Leitão 2010 ; Castiglione et al 2012 ; Rehman et al 2012 ; Zhang et al 2016 ; Chen et al 2018 ), foreign direct investment (Cole et al 2011 ; Sapkota and Bastola 2017 ), and trade variables (Ertugul et al 2016 ; Ozatac et al 2017 ; Park et al 2018 ; Twerefou et al 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…FDI inflows also increase the quality and quantity of human capital (HC) by providing onthe-job training. Although FDI positively affects an economy's growth prospects (EGP), it also adversely affects a country's environmental quality (EQ) (Sapkota & Bastola, 2017;Alvarado, Iñiguez & Ponce, 2017), especially when a country lacks necessary regulations to protect the environment (Hundie & Daksa, 2019;Fan & Hao, 2020). Although many developing countries do not enforce environmental regulations as they are more interested in attracting FDI.…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature suggests that developed countries have strict rules and regulations about environmental decay (ED) (Gerhardter, Prieler, Mayr, Landfahrer, Mühlböck, Tomazic & Hochenauer, 2018). Therefore, they move their industrial operations to "less developed countries (LDC) with less strict environmental regulations (ER), " leading to a phenomenon of industrial flight (Hundie & Daksa, 2019;Sjöman, Autiosalo, Juhanko, Kuosmanen & Steinert, 2018). Unlike the common belief that FDI also contributes to pollution, several researchers believe that foreign companies do not contribute towards environmental decay (ED).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, deposit is also important for economic growth of the economy by channeling into productive investment [3]. Savings and investment play a key role in promoting economic growth [4].…”
Section: 1background Of the Studymentioning
confidence: 99%